Testicular Growth and Pubertal Onset in GH-Deficient Children Treated With Growth Hormone: A Retrospective Study - Cannarella, Rossella; Caruso, Manuela; Crafa, Andrea; Timpanaro, Tiziana Antonia; Lo Bianco, Manuela; Presti, Santiago; Condorelli, Rosita A.; La Vignera, Sandro; Calogero, Aldo E. (Frontiers in Endocrinology, 2021)
The prevalence of apparently idiopathic oligozoospermia has been esteemed as high as ⁓70%. An Italian survey has reported bilateral testicular hypotrophy in 14% of final-year high school students. The search for determinants of testicular growth in childhood is important for the primary prevention of spermatogenic failure. Therefore, this cross-sectional retrospective study aimed to evaluate the effect of GH administration on testicular growth and puberty onset in male patients with GH deficiency (GHD). To accomplish this, the clinical charts of 95 patients with GHD were carefully reviewed. Their mean age at the time of diagnosis was 11.2±2.4 years. GH was administered for 44.0±22.4 months and the onset of puberty was recorded after a mean of 25.8±22.4 months from the first GH administration. As expected, serum insulin-like growth factor 1 (IGF1) levels increased significantly after treatment. Before GH therapy, the Tanner stage was I in 59 out of 70 boys (84.3%), II in 8/70 (11.4%), III in 3/70 (4.3%). No one was on stage IV or V. The mean Tanner stage was 1.19±0.51. At the last visit, the Tanner stage was I in 8/72 boys (11.1%), II in 6/72 (8.3%), III in 6/72 (8.3%), IV in 16/72 (22.2%), and V in 36/72 (50.0%). After GH treatment, the mean Tanner stage was 4.05±1.30 (p<0.01). Patients treated with GH showed a significant testicular volume (TV) growth over time, whereas no growth was observed before GH treatment, despite the age was compatible with a spontaneous start of puberty. At multivariate regression analysis, the duration of treatment was found to significantly influence the percentage of TV increase; alone it explained 62% of its variability. These data highlight the role of GH in enhancing testicular growth and puberty onset, which may likely occur through an IGF1-mediated mechanism. Longitudinal studies are needed to understand whether a poor testicular volumetric growth underlies borderline-low IGF1 serum levels in otherwise healthy children. This knowledge may implement the diagnostic-therapeutic algorithm in case of a lack of testicular growth in childhood.